Parliamentarism in Northern and East-Central Europe in the long eighteenth century
1 online resource.
Keywords: "This volume investigates the history of the representative assemblies of Sweden (the Riksdag), Poland (the sejm) and Hungary (the diaeta) in the final period of the ancien régime. It concentrates on the practices and ideas of parliamentarism and constitutionalism, and examines the ideologies that motivated the members of these parliaments. Attempts at the suppression as well as the restoration of the estates' power in all these three countries are examined, as well as, in the case of Hungary, the establishment of popular representation that eventually replaced the estates. These three early modern representative assemblies have never before been explored systematically in a comparative framework"--